Tools for enhancing resilience and addressing internalized heterosexism: bibliotherapy and cinematherapy in groupwork for individuals who come out as an adult - Carpenter, Beth Counselman; Redcay, Alex; Freeman, Amy (Groupwork, 2019)
This article shares the clinical application of bibliotherapy and cinematherapy as groupwork tools to build social support and to foster resilience among group members of LGBTQIA+ support groups for individuals coming out later in life. Coming out groups for LGBTQIA+ individuals, as well as specific tools and exercises to use within these groups remain under-researched. The importance of fostering resilience through groupwork for those leaving a heterocentric lifestyle is discussed, and suggested books, movies and discussion questions for groupwork are provided. Contra-indications for these exercises are also discussed